Peningkatan ketrampilan pemuda di sekitar Masjid Ash-Siddiq, Umbansari Rumbai Pekanbaru melalui kegiatan pelatihan berbasis teknologi - Mochamad Susantok; Sugeng Purwantoro Edy GS (Unri Conference Series: Community Engagement, 2020)
The Directorate of Youth and Sports of the Ash-Siddiq Islamic Foundation (YIAS) is located at the Ash-Siddiq mosque complex as a center for Islamic activities for the Muslim community in 3 RW 10, 11 and 13 in Umbansari sub-district, Rumbai district, Pekanbaru City. The problem is the lack of trained human resources for publication activities and the lack of youth activities in mosques. The aim of the program is to increase the participation of environmental youth in positive activities as well as to increase the number of congregations praying 5 times a day among youth as an effort to foster and coordinate activities at the YIAS Youth and Sports Directorate. The method of implementing program activities includes the provision of internet services within the Ash-Siddiq mosque as a means of publicizing activities through social media. Then in addition to video editing workshops as technical skills provision to support the YIAS activity publication program. The program results in the form of the impact of increasing youth participation in religious activities such as congregational prayer in mosques which increased by an average of 174.4%. In addition, the increase in publications on social media Facebook, Instagram, and YouTube to an average of 9.6 posts for each YIAS official account on social media. Then the results of the usability survey analysis of the use of internet services and the use of video streaming equipment to publish directly, the results are 90.9% or 4.54 on a scale of 1-5